Nouveaux matériaux nanocomposites dérivés des polysilicates lamellaires. - Binette, Marie-Josée. (University of Ottawa (Canada), 2000)
The intercalation of polyethylene glycol (PEG) into the interlamellar region of magadiite was performed using leading two different methods, leading to interesting new nanocomposites materials. In the first approach, magadiite was acidified and pre-intercalated with DMSO before PEG was inserted in between the layers. In this approach, instead of dissolving the PEG in a solvent, a large excess of polymer was used. This was the first reported example of the intercalation of a polymer in the acidified derivative of magadiite. In the second approach, sodium ions of magadiite were first exchange with octadecylammonium ions (the three different derivatives obtainable were discussed extensively) before PEG was intercalated in the interlayer region. As in the first approach, the PEG intercalation was solvent-free. A pellet consisting of a 50:50 (w/w) mixture of the polymer and the silicate derivative was prepared and heated. In this case two different nanocomposites were formed depending on the temperature at which the pellets were heated. Both methods described lead to the formation of new intercalated nanocomposites. Finally, the synthesis of a polyrotaxane composed of PEG and alpha-cyclodextrin was achieved. The methylation of the polyrotaxane was also performed. The intercalation of both the polyrotaxane and the methylated polyrotaxane was not successful using the first approach described earlier.
Keywords: Chemistry, Inorganic.